2014
DOI: 10.1093/eurheartj/ehu460
|View full text |Cite
|
Sign up to set email alerts
|

Function over form? Assessing the left atrium in heart failure

Abstract: This editorial refers to 'Left atrial function measured by cardiac magnetic resonance imaging in patients with heart failure: clinical associations and prognostic value' † , by P. Pellicori et al., on page 733.The understanding of heart failure (HF) haemodynamics has traditionally focused on left ventricular (LV) structure and function, with the left atrium being viewed simply as a passive transport chamber that empties into the left ventricle. Over the last decade, there has been increasing recognition of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…An inverse relation exists between LA strain and LV end‐diastolic filling pressures and conventional indices of diastolic function . Recently, LA function has gained recognition as an important focus area in the assessment of LV diastolic function, especially in heart failure . We demonstrated that LA reservoir strain was a better predictor of mean PAWP than LAVi, which is currently one of the major indices for structural abnormalities in the ASE/EACVI recommendations and ESC guidelines .…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…An inverse relation exists between LA strain and LV end‐diastolic filling pressures and conventional indices of diastolic function . Recently, LA function has gained recognition as an important focus area in the assessment of LV diastolic function, especially in heart failure . We demonstrated that LA reservoir strain was a better predictor of mean PAWP than LAVi, which is currently one of the major indices for structural abnormalities in the ASE/EACVI recommendations and ESC guidelines .…”
Section: Discussionmentioning
confidence: 79%
“…25 Recently, LA function has gained recognition as an important focus area in the assessment of LV diastolic function, especially in heart failure. 20,21,26,27 We demonstrated that LA reservoir strain was a better predictor of mean PAWP than LAVi, which is currently one of the major indices for structural abnormalities in the ASE/EACVI recommendations and ESC guidelines. 1,13,14 It is suggested that a decrease in LA function might precede LA remodelling 20 and is the best parameter to distinguish asymptomatic patients with diastolic dysfunction from those with HFpEF.…”
Section: Isovolumetric Relaxation Time and Left Atrial Strain As Predmentioning
confidence: 83%
“…It is worth noting that active contraction of LA modulates both LV filling and LV stroke volume. This latter can be increased by ~15-30% in healthy individuals and even more in the presence of abnormal relaxation (Pagel et al 2003, Shah & Lam 2015.…”
Section: Resultsmentioning
confidence: 99%
“…The above relocation of interest to endothelial inflammation shifts attention to concentric LVH remodeling and diastolic dysfunction in contrast to the HFrEF remodeling, which is driven by progressive loss of cardiomyocytes [ 49 ]. Pellicori et al [ 50 ] believe that left atrial emptying function (LAEF) is a better prognostic marker in outpatients referred for HF, while the improvement of the LA structural remodeling after therapy is associated with better clinical outlook in patients with HF [ 51 ].…”
Section: Clinical Progression In Patients With Preserved Ejection mentioning
confidence: 99%
“…The relevant clinical trials are suboptimal in their design, and the treatment to a great extent remains largely empiric [ 1 ]. The present limited natural history data on follow-up in all clinical stages of PDD and HFpEF patients raise a number of questions: (1) there is an unspecified relationship between PDD and progression to HFpEF; (2) there are no data for the relationship between the degree of PDD and clinical progression, as people with the same degree of PDD develop different clinical phenotypes; (3) there is an undetermined connection of the progression rate from PDD to HFpEF for each particular comorbidity; (4) there are no data for similarities or differences between the two clinical phenotypes on clinical deterioration and progression up to the final stages of HF; (5) there are no clear data on the mortality rate of HFpEF patients during the whole period of clinical deterioration up to the final stages; more data are required for the duration and survival in each step of the syndrome ( Figure 2 ); (6) robust data are needed to support the notion that in HFpEF, the left ventricular remodeling is the most probable cause of the clinical decline; (7) it is speculated that the two phenotypes differ in their remodeling mechanism, and as a consequence, they have developed different clinical progression rates; (8) novel prognostic imaging biomarkers are required; probably, LA function is emerging as an important prognostic biomarker [ 51 ].…”
Section: Incomplete Knowledge Of Clinical Progressionmentioning
confidence: 99%